2016
DOI: 10.3329/jbcps.v33i2.28022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Characteristics and Aetiology of Asymptomatic Raised Alanine Aminotransferase in Newly Detected Diabetes and Impaired Glucose Tolerance Patients

Abstract: Objectives: Clinical evaluation and identification of aetiology of asymptomatic raised serum alanine aminotransferase (ALT) level in newly detected adult diabetic and impaired glucose tolerance (IGT) patients.Methods: In this cross-sectional study, newly detected adult diabetic and IGT patients having asymptomatic raised serum ALT level of > 1.5 times of upper limit of normal were evaluated clinically and by laboratory tests.Results: Total number of patients was 120, which was 3.1% of all newly registered diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Serum alanine transaminase which is known as a marker of liver damage was seen to be raised in 12% of the subjects which is similar to the reports of Rahman MM. as 12.33% [24]. This is less when compared to reports by other authors Reza M. as 17 the 'e' antigen negative group because these individuals were in unrecognized disease phase or that the 'e' antigen titer had simply fallen below the threshold levels but not below the threshold functional impact [20].…”
Section: Severalmentioning
confidence: 72%
See 2 more Smart Citations
“…Serum alanine transaminase which is known as a marker of liver damage was seen to be raised in 12% of the subjects which is similar to the reports of Rahman MM. as 12.33% [24]. This is less when compared to reports by other authors Reza M. as 17 the 'e' antigen negative group because these individuals were in unrecognized disease phase or that the 'e' antigen titer had simply fallen below the threshold levels but not below the threshold functional impact [20].…”
Section: Severalmentioning
confidence: 72%
“…Nearly 8% of the tested IDAHS were positive for HBeAg, which similar to the results reported by Puri AS. as 5-37%,Ijoma U as 8.6%, MM Rahman as 9.3% [18,23,24] but less when compared to the reports by Reza. M. 11.7%, K S Rashmi as 12.89%, Malik K. as 15%, Shiha G 18%, V.Dixit as 21%, Kokhar N. as 21%, Rahman M. A as 23% Chan HL as 31% and Chandra et al as 45% [11][12][21][22][25][26][27][28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study from Bangladesh, Mahbub MM et al found that the commonest etiology of raised serum ALT among newly detected DM and IGT patients was NAFLD followed by hepatitis B and C virus infection. 23 Limitations of the study Short study period and small sample size were limitations of current study. Fibroscan and liver biopsy could not be done.…”
Section: Discussionmentioning
confidence: 99%